(untitled) (World Bulletin of Management and Law, 2022)
Corruption in all its forms is a dangerous scourge that can undermine and topple the state, for corruption is the opposite of integrity or integrity, and where narrow personal interest prevails over the public interest to achieve personal goals and benefits. No one can easily detect it because it is a crime of conscience that may not affect or exceed the law when regulations and laws do not affect the spirit of the times, such as bribes, extortion and illegal trade